Этимологии aзербaйджaнских личных имен (Вестник КазНУ. Серия Востоковедения, 2018)
The article is devoted to historical origin of Azerbaijan personalnames, and scientific facts are analysed about the personal names derivedfrom common names as well as proper names, systematization based onanalysis of characteristic examples is described too. Chiefly the place ofonomalogy in linguistics is determined, general theory of proper names,semantics of onomastic units are characterized here.The study aims tolearn the creation of Azerbaijan personal names. In this scientific work theorigin and meaning of personal names are investigated scientifically. Thelinguistic features of onomastic unites have been attracted to the scientificresearch and have been received interesting facts. And also it has beenused from the list of rich literature.